2022
DOI: 10.3390/biomimetics7030137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Antimicrobial Agents Peppermint Essential Oil and Silver Nanoparticles on Bone Cement Properties

Abstract: The main problems directly linked with the use of PMMA bone cements in orthopedic surgery are the improper mechanical bond between cement and bone and the absence of antimicrobial properties. Recently, more research has been devoted to new bone cement with antimicrobial properties using mainly antibiotics or other innovative materials with antimicrobial properties. In this paper, we developed modified PMMA bone cement with antimicrobial properties proposing some experimental antimicrobial agents consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…The maximum temperature observed for MFC-containing ALBC in present research is close to the value observed previously [ 48 ]. Nevertheless, it should be underlined that the direct comparison of the polymerization temperatures from different works might be ambiguous since this parameter also strongly depends on the size/shape of the BC sample, the ratio of monomer to polymer, the conditions of the temperature registration (e.g., in vitro or in vivo studies), as well as the degree of heat waste [ 52 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The maximum temperature observed for MFC-containing ALBC in present research is close to the value observed previously [ 48 ]. Nevertheless, it should be underlined that the direct comparison of the polymerization temperatures from different works might be ambiguous since this parameter also strongly depends on the size/shape of the BC sample, the ratio of monomer to polymer, the conditions of the temperature registration (e.g., in vitro or in vivo studies), as well as the degree of heat waste [ 52 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…One study demonstrated that CA-based composite coatings containing hydroxyapatite (HAp) and Mg particles enhanced the corrosion resistance and hydrophilic characteristics of Mg-based implants. [90,91] The most important things to consider in these polymeric coatings are their chemical and biological compatibility with the host tissue and nontoxicity. There are numerous techniques to fabricate high-throughput polymeric coatings, such as Reproduced with permission from.…”
Section: Polymeric Coatingsmentioning
confidence: 99%
“…Metallic and metallic oxide nanoparticles, including ZnO, copper, silver, gold, and platinum, are commonly known to possess bactericidal properties [64][65][66]. Among these inorganic antibacterial agents, silver ions and compounds were extensively investigated and studied [67][68][69][70]. Silver nanoparticles (AgNPs) possess the capability to interact with a diverse range of microorganisms, including mature bacterial biofilms.…”
Section: Introductionmentioning
confidence: 99%